FEMINIST APPROACH TO UNDERSTANDING SEXUAL BEHAVIOR ON JENNY LIVESTREAM NIMO TV - Putra, Setya Wardana; Weda, Sukardi; Mahmud, Murni (ELITERATE : Journal of English Linguistics and Literature Studies, 2025)
This research aimed to find out sexual behavior on jenny livestream by using feminist approach. This research method used descriptive qualitative, namely the process of processing data by selecting and simplifying the data, then analyzing and compiling it systimatically so that conclusion can be drawn. The sources were from jenny livestream replay on youtube. Mainly on Jenny livestream shows interaction beetwen audience and Jenny until when audience give some virtual gift on her livestream she ended give a nice thanks or doing some erotic moves. The result of study shows six type of verbal language and also elaborate with non verbal language by erotic moves using by jenny in her livestream. The result of the research also showed different reaction by audience when watch jenny livestream and and based on the views of the two feminists (Tong and Millet,) that  Jenny’s sexual behavior in the form of erotic movements displayed on social media as a form of individual freedom in expressing her sexuality and challenging traditional norms in society.